Acceptability and feasibility of the CHARISMA counseling intervention to support women's use of pre-exposure prophylaxis: results of a pilot study - Ellen K. Wilson; L. Danielle Wagner; Thesla Palanee-Phillips; Sarah T. Roberts; Elizabeth E. Tolley; Florence Mathebula; Laura Pascoe; Michele Lanham; Rose Wilcher; Elizabeth T. Montgomery; the CHARISMA team (BMC, 2021)
Abstract Background Women may need or seek male partner approval to safely and consistently use oral antiretroviral pre-exposure prophylaxis (PrEP) or vaginal microbicides. We developed CHARISMA, a counseling intervention to support women's relationships and their ability to consistently use HIV prevention products. Methods In a pilot study with 95 female participants in Johannesburg, South Africa, lay counselors implemented CHARISMA, assessing participants' relationship(s) with their male partner(s) and barriers or facilitators to HIV prevention method use, and then providing tailored, interactive counseling. We conducted study participant surveys and clinic staff interviews to evaluate CHARISMA's feasibility and acceptability. Results The CHARISMA pilot study indicates that a two-session relationship counseling intervention with 6-month follow-up to support women's ability to safely and effectively use vaginal microbicides was generally acceptable and feasible. Most participants thought CHARISMA was relevant, helpful, and about the right length, and that it had a positive impact on their relationships with their partners and their product use. Staff estimated that the intervention took 1.5-2 h to implement at enrollment and 45 min to an hour for the month 1 visit. They thought that overall CHARISMA was generally feasible to implement. Conclusions Findings from this study suggest several lessons learned that may be relevant to others developing interventions supporting women's use of oral PrEP or vaginal microbicides. The use of lay counselors instead of nurses to deliver counseling appeared to be successful, but the counselors experienced significant stress from hearing about participants' traumatic experiences and required emotional support to avoid burnout. Although staff and participants felt that having multiple intervention sessions over time was valuable, a similar level of intensity may not be feasible in other settings. Further research is needed to determine an intervention delivery mode and follow-up period that optimally balances participant needs and clinic resources. Male engagement was a challenge, as it has been in previous studies of vaginal microbicides. Alternative strategies to reach men that do not require them to come to the clinic or rely on their female partners may be more effective.